Enantioselective Hydrogenation of the Double Bond of Exocyclic α, β‐Unsaturated Carbonyl Compounds Catalyzed by Iridium/H8‐BINOL‐Derived Phosphine‐Oxazoline Complexes. Issue 7 (16th April 2014) - Li, Qing; Wan, Pin; He, Yuwei; Zhou, Yougui; Li, Lanning; Chen, Bin; Duan, Kun; Cao, Rihui; Zhou, Zhongyuan; Qiu, Liqin
Abstract H8‐BINOL‐derived phosphine‐oxazolines complexed with iridium were successfully applied for the asymmetric hydrogenation of the carbon‐carbon double bond of exocyclic α, β‐unsaturated carbonyl compounds. A valuable series of α‐chiral cyclic ketones, lactones, and lactams were therefore provided via the reaction in high yields and good to excellent enantioselectivity of up to 95 % ee. The effects of the ligands and substrate structures on the asymmetric catalysis were also discussed.